A density functional theory study of the hydrogenation and reduction of the thio-spinel Fe3S4111 surface. Issue 5 (17th January 2019) - Roldan, Alberto; de Leeuw, Nora H.
Abstract : Greigite shows promise as a reduction catalyst and it is, therefore, essential to understand its surface chemistry under reducing conditions. Abstract : The mineral greigite, Fe3 S4, shows promising electro-reduction activity, especially towards carbon dioxide conversion to small organic molecules. We have employed density functional theory calculations with correction for the long-range dispersion forces to investigate the behavior of hydrogen on the greigite111 surface. We have studied the adsorption, diffusion, surface reduction and associative ( i.e. Volmer–Tafel mechanism) and molecular desorption of hydrogen as a function of its coverage. We found that (i) the H ad-atoms adsorb on S sites far from metallic centres in the topmost surface layer; (ii) the reduction of greigite by hydrogen is energetically unfavorable at any surface coverage; and (iii) molecular hydrogen evolution has a transition state at ∼0.5 eV above the energy of the reactants on Fe3 S4 111, which is very similar to the barrier found experimentally on Pt111. We have also determined the electrode potential under room conditions at which the H2 evolution reaction becomes energetically barrierless.